Filosofía y método: vías de contemplación en Plotino - Hermoso Félix, María Jesús (Pontificia Universidad Católica del Perú, 2025)
This paper explores Plotinus’ methodological approach considering the practical perspective of his philosophy. According to Plotinus, there is something in us that is permanently oriented towards the intelligible realm (En. IV 8. 8. 5). Contemplation is a continual activity for the soul. We do not cease to contemplate; our being and our individuality depend on it. However, this activity often goes unnoticed (En. I 1. 11. 9). The possibility of becoming aware of it opens up a complex and challenging itinerary of philosophical exercise, present in the whole Platonic tradition. This paper will examine the various paths designed to facilitate contemplation, as well as the roles of imagination and memory in these processes.

Este artículo tratará de introducirse en la propuesta metodológica de Plotino, en el ángulo práctico de su filosofía. Hay algo en nosotros que está vuelto permanentemente hacia lo inteligible (En. IV 8. 8. 5). La contemplación es para el alma una actividad continua, no dejamos de contemplar, de ello depende nuestro ser y nuestra individualidad. Sin embargo, esta actividad pasa desapercibida en la mayoría de los casos (En. I 1. 11. 9). La posibilidad de su percepción abre el complejo y esforzado camino del ejercicio filosófico, presente en toda la tradición platónica. Exploraremos las diferentes vías pensadas para favorecer la contemplación y el modo en que se ven implicadas la imaginación y la memoria.
Philosophy and Method: Paths of Contemplation in Plotinus
Keywords: Plotinus; Enneads; Philosophical exercise; Contemplation; Perception; Plotino; Enéadas; Ejercicio filosófico; Contemplación; Percepción; https://purl.org/pe-repo/ocde/ford#6.03.01